Estudo dos traumatismos alveolodentários na dentição decídua - Costa, Vanessa Polina Pereira da (2012)
Even with the traumatic dental injury in primary teeth not given due importance, since the majority published studies in the literature refer to the permanent dentition, their study is justified by the high prevalence and consequences caused not only to their own primary teeth, as well as the permanent dentition. The aim of this research is evaluate the distribution of traumatic dental injuries in children treated at the Center of Studies and Treatment of Traumatic Dental Injuries in the Primary Dentition (NETRAD) School of Dentistry, UFPel- Pelotas, and other variables related to demographic data and specific injury. These data was obtained through the analysis of patient records containing medical history, clinical and radiographic examination also photographic records. Patients were included in the sample if they have complete patient records, including the authorization from parents and/or guardian. Among 707 children attending the service since May 2002 to July 2011, 603 were included in the study with aged between 8 and 89 months and these presented 1043 injured teeth. The boys had more injuries than girls (1.4:1). Children 2-3 years had the highest number of injuries. The most prevalent cause was the fall, with two or more teeth involved, especially the maxillary central incisor. The child s home was the principal place of occurrence and the type of injury most common was subluxation, followed by avulsion and intrusion. The severe injuries were the most prevalent (45.5%) accompanied by mild (33.7%). Teeth evaluated, 52.7% had clinical sequelae and 32.7% radiographic sequelae. Among the mineralized tissue injuries involving fistula/swelling, followed by the change of color were the most prevalent clinical sequelae and the radiographic sequelae, periapical radiolucency was the most prevalent. Among injuries involving the supporting tissues of the ectopic position and early loss were the most prevalent clinical sequelae and accelerated root resorption among the most prevalent radiographic. Thus, it is necessary to be trained professionals to meet all types of trauma in young children, taking into account the consequences which may occur in any injuries involving both in the mineralized tissues, as in the surrounding tissues support